Gender Differences in Chronic Obstructive Pulmonary Disease Symptom Clusters - Zhang, Haihong (Int J Chron Obstruct Pulmon Dis, 2021)
PURPOSE: Previous research has indicated that female and male patients may experience different levels of symptoms. However, no studies of chronic obstructive pulmonary disease (COPD) patients have compared the number and types of symptom clusters identified in male and female patients. Therefore, the purpose of this study was to investigate gender differences in symptom clusters among COPD patients. PATIENTS AND METHODS: A total of 371 eligible patients were enrolled in the study. We assessed nine COPD symptoms, namely, dyspnea, cough, sputum, chest tightness, sleep quality, fatigue, frailty, anxiety, and depression. Exploratory factor analyses were used to explore the underlying clusters of the COPD symptoms. RESULTS: Underlying the nine symptoms, female patients had 2 clusters, and male patients had 3 clusters. Specifically, the three general symptoms poor sleep, fatigue, and frailty loaded on the same symptom cluster with anxiety and depression in female patients, while the same 3 general symptoms loaded on the same symptom cluster with chest tightness and dyspnea in male patients. Moreover, cough and sputum not only were more common in male patients but also loaded together on a separate symptom cluster. CONCLUSION: Our findings suggest that in order to improve fatigue, frailty, and poor sleep quality, symptom management strategies should more closely address anxiety and depression in female patients as well as chest tightness and dyspnea in male patients. Smoking cessation is particularly important in male COPD patients because they account for a much higher proportion of smokers and are more likely to have cough and sputum. These findings signify the importance of identifying and implementing gender-tailored symptom management strategies to relieve symptom burden in COPD patients to enhance their quality of life.